2013
DOI: 10.7314/apjcp.2013.14.3.2147
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological Cancer Services in Arab Countries: Present Scenario, Problems and Suggested Solutions

Abstract: Gynecological malignancies account for 9% of all female cancers worldwide. In the Arab countries Breast cancer is the leading cancer in women followed by cervical cancer. Ovarian cancer ranks as fourth leading cancer in women. There are huge differences in the available resources among Arab countries. However the challenges facing the provision of gynecological cancers services shared similarities like the cultural and religious background. Most of the gynecological cancers are diagnosed at a later stage in Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…This finding of more advanced tumor presentation of BC in BA patients concurs with two previous reports on Palestinian patients residing in the Jerusalem area, and in Arab patients residing in northern Israel (Zidan et al, 2012). A late stage at presentation and locally-advanced BC has typically been reported in studies from Arab countries (Ortashi, 2013), and has been ascribed in these studies to failure to seek medical attention for early but palpable BC (Donnelly et al, 2013). Cultural reluctance to participate in screening mammography programs in the Arab population has been mentioned as a major impediment for early diagnosis of BC in these countries (Bener et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This finding of more advanced tumor presentation of BC in BA patients concurs with two previous reports on Palestinian patients residing in the Jerusalem area, and in Arab patients residing in northern Israel (Zidan et al, 2012). A late stage at presentation and locally-advanced BC has typically been reported in studies from Arab countries (Ortashi, 2013), and has been ascribed in these studies to failure to seek medical attention for early but palpable BC (Donnelly et al, 2013). Cultural reluctance to participate in screening mammography programs in the Arab population has been mentioned as a major impediment for early diagnosis of BC in these countries (Bener et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…However, in the present analysis the difference of occurrence of breast, uterine cervix and ovarian cancers in urban-rural settings was not significant (p>0.05). Women with gynecological cancers especially uterine cervix cancer may report late due to stigma (Ortashi and Kalbani, 2013) and also, because of illiteracy. In our present analysis, the highest proportions (43.5%) of cases with uterine cervix patients were illiterates.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen papers were assessed as potentially relevant. Two were related to general gynecological cancer services in Arab countries (Ortashi & Al Kalbani, ) and general cancer control in the Gulf (Al‐Othman et al, ). Empirical research was not reported in two papers (Al‐Mandeel et al, , K. Sait, Bentley, Anfinan, & Power, ), leaving 13 for inclusion in the integrative review.…”
Section: Methodsmentioning
confidence: 99%